2012
DOI: 10.1038/nsmb.2434
|View full text |Cite
|
Sign up to set email alerts
|

Phf19 links methylated Lys36 of histone H3 to regulation of Polycomb activity

Abstract: Polycomb-group proteins are transcriptional repressors with essential roles in embryonic development. Polycomb repressive complex 2 (PRC2) contains the methyltransferase activity for Lys27. However, the role of other histone modifications in regulating PRC2 activity is just beginning to be understood. Here we show that direct recognition of methylated histone H3 Lys36 (H3K36me), a mark associated with activation, by the PRC2 subunit Phf19 is required for the full enzymatic activity of the PRC2 complex. Using N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
254
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 220 publications
(264 citation statements)
references
References 71 publications
10
254
0
Order By: Relevance
“…3a, b), similar to the results from isolated Tudor domains 4,6,7,11,15,16 , suggesting that the presence of the other domains does not interfere with the histone binding preference. In addition, we confirmed that the Tudor domains rather than the PHD1/2 fingers are responsible for the above recognition, as mutation of an aromatic-cage residue in the Tudor domain (Y47A for PHF1, Y62A for MTF2) led to a complete loss in binding affinity (Extended Data Table 2).…”
supporting
confidence: 81%
See 4 more Smart Citations
“…3a, b), similar to the results from isolated Tudor domains 4,6,7,11,15,16 , suggesting that the presence of the other domains does not interfere with the histone binding preference. In addition, we confirmed that the Tudor domains rather than the PHD1/2 fingers are responsible for the above recognition, as mutation of an aromatic-cage residue in the Tudor domain (Y47A for PHF1, Y62A for MTF2) led to a complete loss in binding affinity (Extended Data Table 2).…”
supporting
confidence: 81%
“…Polycomb-like proteins (PCLs), including PHF1, MTF2 and PHF19, are PRC2 associated factors that form sub-complexes with PRC2 core components 3 , and have been proposed to modulate PRC2’s enzymatic activity or its recruitment to specific genomic loci 413 . Mammalian PRC2 binding sites are enriched in CG content, which correlate with CpG islands that display a low level of DNA methylation 14 .…”
mentioning
confidence: 99%
See 3 more Smart Citations